1977
DOI: 10.1073/pnas.74.12.5744
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of reovirus virulence: Role of the S1 gene

Abstract: A genetic approach has been used to define the molecular basis for the different patterns of virulence and central nervous system cell tropism exhibited by reovirus types 1 and 3. Intracerebral inoculation of reovirus type 3 into newborn mice causes a necrotizing encephalitis (without ependymal damage) that is uniformly fatal. Animals inoculated with reovirus type 1 generally survive and may develop ependymal cell damage (without neuronal necrosis) and hydrocephalus. Using recombinant clones derived from cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
191
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(194 citation statements)
references
References 15 publications
2
191
1
Order By: Relevance
“…Thus, it is probable that the virus surface antigens responsible for cell attachment determine the tropism of the virus and the other virus genes play a role in regulating expression within a given cell. Furthermore, it has been demonstrated that the reovirus gene $4, which controls the shut-offof host cell metabolism, is implicated in the ability to provoke persistent infections (Weiner et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is probable that the virus surface antigens responsible for cell attachment determine the tropism of the virus and the other virus genes play a role in regulating expression within a given cell. Furthermore, it has been demonstrated that the reovirus gene $4, which controls the shut-offof host cell metabolism, is implicated in the ability to provoke persistent infections (Weiner et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Following oral inoculation into newborn mice, serotype 1 (T1) 1 reovirus strains spread hematogenously to the central nervous system and replicate within ependymal cells, resulting in hydrocephalus. In contrast, serotype 3 (T3) reovirus strains utilize neural spread pathways to gain access to the central nervous system, where they replicate in a wide variety of neurons and cause encephalitis (15,16). Since reovirus contains a segmented genome, it is possible to link pathogenic phenotypes to individual viral genes using reassortant viruses.…”
mentioning
confidence: 99%
“…Three segments encode the three outer capsid polypeptides: M2 encodes ,ul/,ulC, Si encodes or, and S4 encodes u3 (4,5). Prior studies have demonstrated that the Si ds RNA segment [encoding the viral hemagglutinin (HA)] is the viral component responsible for cell and tissue tropism and specificity ofinteraction with the host immune system, presumable by an interaction of the viral hemagglutinin with specific receptors on host tissues (6)(7)(8). The Si ds RNA segment is thus responsible' for differences in the pattern of neurovirulence between type 1 and type 3; type 3 causes lethal encephalitis ("neurotropic") whereas type 1 causes benign ependymitis ("non-neurotropic") (6).…”
mentioning
confidence: 99%
“…Prior studies have demonstrated that the Si ds RNA segment [encoding the viral hemagglutinin (HA)] is the viral component responsible for cell and tissue tropism and specificity ofinteraction with the host immune system, presumable by an interaction of the viral hemagglutinin with specific receptors on host tissues (6)(7)(8). The Si ds RNA segment is thus responsible' for differences in the pattern of neurovirulence between type 1 and type 3; type 3 causes lethal encephalitis ("neurotropic") whereas type 1 causes benign ependymitis ("non-neurotropic") (6). In contrast to these differences in virulence between serotypes 1 and 3, which are based on the localization of the different reovirus serotypes in different target tissues, the basis for variations in virulence of isolates within a serotype (and thus having the same tropism) has not been studied.…”
mentioning
confidence: 99%